Muzyka jako Sztuka Czysta. Stanisław Ignacy Witkiewicz i Konstanty Regamey - Sokół, Lech (Przestrzenie Teorii, 2010)
Sokół Lech, Muzyka jako Sztuka Czysta. Stanisław Ignacy Witkiewicz i Konstanty Regamey [Music as Pure Art. Stanisław Ignacy Witkiewicz and Konstanty Regamey]. „Przestrzenie Teorii” 14. Poznań 2010, Adam Mickiewicz University Press, pp. 33-84. ISBN 978-83-232- 2210-1. ISSN 1644-6763. In Witkacy’s aesthetics, the problem of the essence, function and status of music in the system of pure arts has never been finally resolved. Many important questions remained unanswered. In spite of numerous announcements, Witkacy never developed a theory of music. To an extent, this work was unexpectedly carried out by Konstanty Regamey (Constantin Regamey, 1907–1982), Polish-Swiss composer, critic, theorist of music, linguist and India specialist, who for some time was a friend of Witkacy and admitted to being associated with the latter’s aesthetics. In 1933 Regamey published a study Treść i forma w muzyce [Content and Form in Music] which on a number of points follows closely not only Witkacy’s ideas but even his stylistics. In my opinion, yet another essay by Regamey should be taken into consideration in sketching relations between his and Witkacy’s theories of music; it is Próba analizy ewolucji w sztuce [An Attempt at Analysis of Evolution in Art]. The inclusion of these and other issues relating to music in a more detailed discussion of Witkacy’s aesthetics allows us both to understand this aesthetics better, and to dispel some of the hastily made and still unanswered criticisms.